2023
DOI: 10.3390/ma16175883
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Behavior of the FGH96 Superalloy under High-Temperature Cyclic Loading

Zhengguang Li,
Haiqin Qin,
Kejun Xu
et al.

Abstract: Strain-controlled low-cycle fatigue (LCF) tests and stress-controlled creep-fatigue interaction (CFI) tests on the FGH96 superalloy were carried out at 550 °C to obtain the cyclic softening/hardening characteristics at different strain amplitudes and ratcheting strain characteristics under different hold time. The failure mechanism of the FGH96 superalloy under different loading conditions was analyzed through fracture observations. The results show that the FGH96 superalloy exhibits different cyclic softening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In the previous study, our research group explained the link between the microscopic fracture mechanism and the cyclic softening/hardening behavior of the FGH96 superalloy [21]. In this section, the micro-mechanisms summarized in the previous study will be combined to analyze the different properties exhibited by the FGH96 superalloy under different strain amplitudes from the perspective of internal stress evolution.…”
Section: Microscopic Mechanism Of Internal Stress Evolutionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, our research group explained the link between the microscopic fracture mechanism and the cyclic softening/hardening behavior of the FGH96 superalloy [21]. In this section, the micro-mechanisms summarized in the previous study will be combined to analyze the different properties exhibited by the FGH96 superalloy under different strain amplitudes from the perspective of internal stress evolution.…”
Section: Microscopic Mechanism Of Internal Stress Evolutionmentioning
confidence: 99%
“…By comparing various curves, it can also be found that with the increase in strain amplitude, the peak stress σ max in the stable section gradually increases, while the fatigue life shows a downward trend. In previous work [21], our research group carefully analyzed the different cyclic response characteristics of the FGH96 superalloy in the early cycles through the stress-strain hysteresis curves under various strain amplitudes. Next, the cyclic softening/hardening characteristics of the FGH96 superalloy in the early cycles will be analyzed from the perspective of the relationship between the half-life hysteresis curves and the uniaxial tensile curve.…”
Section: Cyclic Softening/hardening Propertiesmentioning
confidence: 99%
See 1 more Smart Citation